The commercialisation decisions of research-based spin-off: Targeting the market for technologies - Conceição, O.; Fontes, M.; Calapez, T. (Technovation, 2012)
his paper addresses the commercialisation decisions of research-based spin-off firms (RBSOs), focusing on the case of companies specialising in the production and sale of intellectual property a model of entrepreneurial behaviour increasingly frequent in science-based fields and that research-based spin-offs may be more prone to adopt, given their specific characteristics. Combining insights from the economics of technological change and the strategic management of technology literature, we discuss the conditions that can influence firms' ability to operate in the market for technology, and advance some theory-driven hypotheses regarding key factors that are likely to determine it - nature of knowledge being exploited, appropriability conditions, location and degree of control upon complementary assets and institutional setting of origin - as well as their impact upon firms' decisions. These hypotheses are tested on a group of 80 European RBSOs, using data collected specifically for this purpose, on the basis of questionnaire-based interviews. This research adds to recent work on the determinants of the commercialisation strategy of technology-based SMEs, but by focusing on a particular group of companies - the RBSOs - we also take into consideration some distinctive characteristics of this group, which introduce some specificity in their innovative behaviour.